A institucionalização da língua padrão na China maoísta e o ensino de história - Sousa, Anderson Nogueira (My University, 2026)
This study investigates the institutionalization of the standard language in Maoist China, understanding this process as part of the broader dynamics of state-building, educational reorganization, and political centralization promoted by the Peoples Republic of China between 1949 and 1976. The research is based on the assumption that language standardization was not merely a technical or administrative measure, but rather an integral component of a wider project of national unification, mass literacy, and social mobilization. To develop this analysis, the study revisits historical precedents concerning the relationship between writing, power, and unity in China, examining the role of the literati tradition, imperial examinations, and the so-called officials speech in shaping long-term processes of cultural and political centralization. It then analyzes, within the Maoist context, the promotion of Putonghua as a common language, the simplification of Chinese characters, the creation of Hanyu Pinyin, and the integration of language into the political campaigns of the period, highlighting how linguistic policy was closely linked to institutional reorganization and ideological dissemination. Methodologically, the research adopts a historical-interpretative approach based on bibliographic analysis and engages with authors who discuss Chinese language history, language policy, and nation-building processes. As a practical outcome, and in accordance with the professional masters framework, the study also presents an educational product: a teachers manual in e-book format aimed at supporting the teaching of Chinese history in basic education. By articulating language, writing, power, state, and teaching, this dissertation seeks to contribute both to the historical understanding of the Chinese experience and to the expansion of didactic possibilities for approaching modern China in history education. [resumo fornecido pelo autor]
Este trabalho investiga a institucionalização da língua padrão na China maoísta, compreendendo esse processo como parte da construção do Estado, da reorganização educacional e da centralização política promovidas pela República Popular da China entre 1949 e 1976. O estudo parte da compreensão de que a padronização linguística não se limitou a uma medida técnica ou administrativa, mas integrou um projeto mais amplo de unificação nacional, alfabetização e mobilização social. Para desenvolver essa análise, a pesquisa retoma antecedentes históricos da relação entre escrita, poder e unidade na China, abordando o papel da tradição letrada, dos exames imperiais e da chamada fala dos oficiais na formação de uma longa experiência de centralização cultural e política. Em seguida, examina, no contexto maoísta, a promoção do Putonghua como língua comum, a simplificação dos caracteres, a criação do hanyu pinyin e a inserção da linguagem nas campanhas políticas do período, evidenciando como a língua se articulou aos esforços de reorganização institucional e de difusão ideológica do novo regime. A pesquisa adota abordagem histórico-interpretativa de base bibliográfica e dialoga com autores que discutem a história da língua chinesa, a política linguística e os processos de construção nacional. Como desdobramento prático, e em consonância com a proposta do mestrado profissional, o trabalho apresenta também um produto educacional: um manual do professor, em formato de e-book, voltado ao ensino de História da China na educação básica. Ao articular língua, escrita, poder, Estado e ensino, a dissertação busca contribuir tanto para a compreensão histórica da experiência chinesa quanto para a ampliação das possibilidades didáticas de abordagem da China moderna no ensino de História. [resumo fornecido pelo autor]
Keywords: História - Estudo e ensino; Política linguística; China - História; Língua chinesa - Escrita; Estado; History - Study and teaching; Language policy; China - History; Chinese language - Writing; State; The